Activity of 1-(2'-fluoro-2'-deoxy-beta-D-arabinofuranosyl)thymine against herpes simplex virus in cell cultures and rabbit eyes. - Trousdale, M D (1983)
A new antiviral compound 1-(2'-fluoro-2'-deoxy-beta-D-arabinofuranosyl)thymine (2'-fluoro-5-methyl-ara-uracil [FMAU]), was compared with acyclovir and idoxuridine in vitro against two strains of both herpes simplex virus type 1 (HSV-1) and HSV-2. Determinations of the 50% effective dose varied slightly with each strain and with the host cells employed. The 50% effective dose for FMAU and acyclovir against HSV-1 ranged from 0.1 microM to 0.5 to 0.6 microM in rabbit kidney cells and from 0.5 microM to 0.6 to 0.78 microM in Vero cells. Beginning 4 days post-inoculation, topical FMAU therapy given five times per day to rabbits with acute herpetic keratitis either suppressed or delayed the severity of corneal epithelial involvement, conjunctivitis, iritis, and corneal clouding. Responses to treatment with FMAU were similar to those obtained with acyclovir and significantly better than those attained with idoxuridine and vidarabine. At 30 to 40 days after the end of treatment, rabbit eyes were subjected to iontophoresis with epinephrine in an attempt to induce reactivation and enhance detection of previously latent HSV-1. Latent HSV-1 was detected in 67 to 92% of trigeminal ganglia in FMAU-treated animals and in 90% of placebo-treated animals.